Pernikahan Wanita Hamil karena Perzinahan (Studi Perbandingan Antara Madzhab al-Arba’ah dan Kompilasi Hukum Islam): Marriage of a Pregnant Woman Due to Adultery (A Comparative Study Between the Madzhab al-Arba’ah and the Compilation of Islamic Law) - Bakry, Kasman; Armida Abdurrahman; Fariyanti, Fariyanti (DIRASAH: Jurnal Kajian Islam, 2024)
Marriage of a pregnant woman due to adultery is a woman who becomes pregnant due to adultery before carrying out the marriage contract, then is married to the man who impregnated her. Seeing the facts now, many women become pregnant outside of marriage, because of the excessive freedom of association between men and women, without thinking, what if pregnancy occurs. In Islamic law, people who have sexual relations outside of marriage are punished for adultery, if a woman who commits adultery becomes pregnant, then the scholars Imam a-Syafi'i, Imam abu Hanifah, Imam Malik, and Imam Ahnad bin Hanbal have different opinions, whether a woman who is pregnant due to adultery may marry the man who impregnated her or another man or not. While in the Compilation of Islamic Law, the permissibility of pregnant marriage is seen from Article 53 paragraph (1) of the Law. This permissibility is based on considerations related to the aim of maintaining the welfare of the baby she is carrying in order to maintain the honor of her lineage so that it is not mixed with the sperm of another man, and of course also to maintain the child's survival.